Analisis Pelaksanaan Pembelajaran PPKN dalam Pembentukan Karakter Siswa SMPN 26 Takengon Kecamatan Linge Kabupaten Aceh Tengah - Rizkan Wan Ramadhan; Murthada Murthada; Alfiandi Zikra (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Pancasila and Citizenship Education (PPKn) is a learning process that aims to instill the values ​​of Pancasila as the foundation of the state and the outlook on life of the Indonesian nation to all citizens, especially the younger generation. PPKn has a very crucial role in shaping students' character. This subject not only teaches knowledge about the state and government, but also instills the noble values ​​of Pancasila which are expected to be a guideline for students' lives who are currently experiencing many character shifts in student life. This study aims to: (1) analyze the implementation of PPKn learning in shaping students' character, and (2) determine the challenges faced by PPKn teachers in shaping the character of students at SMPN 26 Takengon. This study is a descriptive qualitative study. The data source sample was taken using the Purposive sampling technique. The research variables include the implementation of PPKn learning and student character. Data collection techniques used interviews, documentation, and observation. The results of the study showed that First, the implementation of PPKn learning carried out by teachers in the classroom has included character values, the formation of character values ​​is good but there is no periodic evaluation; Second, the factors that hinder character formation are students' lack of understanding of character, lack of PPKn lesson hours, lack of PPKn teachers; Third, ways to minimize obstacles are to provide students with an understanding and examples of character values, make periodic evaluations, increase lesson hours and increase the number of PPKn teachers.